INTERNALISASI PERILAKU SOPAN SANTUN MELALUI MEDIA PEMBELAJARAN VIDEO ANIMASI - Ella Rodia; Rido Kurnianto; Zahid Zufar At Thaariq (International Journal of Learning and Education, 2025)
This study aims to explore the internalization of polite behavior through animated video learning resources at SMKN 2 Ponorogo. It investigates the impact of these media on shaping students' polite behavior. Utilizing a qualitative phenomenological approach, data was collected through interviews, observations, and documentation, and presented descriptively with narrative texts from illustrators. The findings reveal that the internalization of polite behavior via animated videos occurs in three phases: 1) value change, where students grasp the learning material; 2) value transaction, where teachers demonstrate concepts through videos; and 3) value instillation, which influences both students and their personalities. The effects noted include students' understanding of politeness, observable improvements in their behavior at home and school, and the application of polite behavior in daily life. This encompasses speaking respectfully, honoring teachers and parents, dressing appropriately, and practicing the 3S (smile, greet, salute), along with religious practices like the Dhuha prayer and reciting Surah Yasin and Surah Ar-Rahman. A significant contribution of this study is its focus on the SMKN level, contrasting with previous research conducted at the SDN level, highlighting notable changes in student habits